Digital Marketing, Price Perception, and Service Quality as Determinants of Customer Loyalty: Evidence From Devasa Studio Salon in Denpasar - Hermyanti Hermyanti; Ni Putu Nita Anggraini; Ni Wayan Eka Mitariani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
Advances in digital technology and increasing competition in the beauty services industry require salons to optimize their marketing strategies to build customer loyalty. This study aims to analyze the influence of digital marketing, price perception, and service quality on customer loyalty at Salon Devasa Studio Denpasar. This study aims to determine the influence of digital marketing, price perception, and service quality on customer loyalty. The research method used is quantitative. The population consists of Salon Devasa Studio customers, with a sample size of 105 people. Data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, multiple correlation analysis, the coefficient of determination, the F-test, and the t-test. The results indicate that digital marketing, price perception, and service quality each have a positive and significant influence on customer loyalty. The researcher’s recommendation is that Salon Devasa Studio should create more engaging posts about customer experiences or attractive offers, establish pricing policies that better align with treatment outcomes, and consistently monitor employees to ensure they provide services as promised, striving to consistently deliver high-quality service at competitive prices.